2006
DOI: 10.2134/agronj2005.0253
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cereal Nitrogen Requirements Derived by Optical On‐the‐Go Sensors on Heterogeneous Soils

Abstract: Variable N management is one of the most promising practices of precision agriculture to optimize nitrogen-use efficiency (NUE) and decrease environmental impact of agriculture. The objective of this study was to test the performance of fertilization in winter wheat (Triticum aestivum L.) and triticale (Triticosecale Wittm.) determined by reflection measurements of on-the-go sensors under heterogeneous field conditions. In 2004 geo-referenced yield and N fertilization data were collected in four heterogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 12 publications
1
38
0
1
Order By: Relevance
“…As most commercially available sensors are based on the signals of a single sensor, this can lead to misinterpretation of the situation in the field (Zillmann et al, 2006). Samson et al (2000) showed that nitrogen and sulphur deficiencies have different effects on the laser-induced fluorescence spectral signatures of a field sensor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As most commercially available sensors are based on the signals of a single sensor, this can lead to misinterpretation of the situation in the field (Zillmann et al, 2006). Samson et al (2000) showed that nitrogen and sulphur deficiencies have different effects on the laser-induced fluorescence spectral signatures of a field sensor.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, this leads to misinterpretation of the truth for variability or heterogeneity (Zillmann et al, 2006). In order to strengthen the reliability of implemented sensor signals, the idea of using a combination of sensors is gaining popularity.…”
Section: Introductionmentioning
confidence: 99%
“…Lammel et al (2001) point out that the Yara N-sensor is valuable to avoid over-and under fertilization within a field resulting in increased yield, decreased lodging and more homogenous ripening. Other researchers accentuate that usage of the N-sensor only have resulted in small differences in yield (Berntsen and Thomsen et al 2006;Jørgensen et al 2006) and Zillmann et al (2006) point out that the N-sensor technology work when nitrogen is the main growth-limiting factor. The usage of Yara N-sensor reduces nitrogen leaching if areas with lower requirements for nitrogen fertilization within the field can be identified (Delin and Stenberg 2014).…”
Section: Experiences From Swedenmentioning
confidence: 99%
“…They showed variable-rate N applications would result in significant N savings compared to uniform N application, when using N priced at $0.55 kg −1 . Researchers in Europe and elsewhere (Schroder et al, 2000;Olfs et al, 2005;Berntsen et al, 2006;Tremblay and Belec, 2006;Zillmann et al, 2006) have also shown that this approach can be used to direct variable in-season N applications in cereal grains that improves NUE, crop harvest ability, and/or quality. Some of the aforementioned research involved use of the Yara N sensor system for variable N applications, which has been available for about a decade in Europe (Yara UK Limited, Lincolnshire, UK) as a commercialized service, and is being adopted by growers.…”
Section: Ground-based Remote Sensingmentioning
confidence: 99%